Translation and cross language validation of human immunodeficiency virus stigma scale in a Pakistani context - Faiza Nayyer; Iffat Batool (Journal of the Pakistan Medical Association, 2021)
Objectives: To evaluate the translation and validation of human immunodeficiency virus stigma scale in Urdu language. Methods: The evaluation study was conducted in Lahore, Kasur, Gujranwala and Faisalabad from January 2019 to June 2019. Forward-backward translation method was used to translate the human immunodeficiency virus stigma scale from English to Urdu. Additionally, inter-correlation among variables was assessed by using correlation to determine the psychometric properties. Exploratory factor analysis of the scale was done followed by confirmatory factor analysis for establishing a good model fit. Results: Cronbach’s alpha coefficient was 0.95. There was high correlation among the sub-components of the the scale, ranging from 0.38 to 0.80 (p<0.001). Confirmatory factor analysis depicted good model fit. Conclusion: The Urdu version of the human immunodeficiency virus stigma scale was found to be a valid and reliable tool to measure personal stigma, disclosure concern, concerns about public attitude and negative self-image. Key Words: HIV/AIDS stigma, Translation, Cross-validation. Continuous...